Strategi Employee Relations PT. Resultan Karya Indonesia (Rekanesia) dalam Memotivasi Kerja Karyawan - Khairunnisa Puspa Mahardika; Hari Eko Purwanto (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
The success of a company is not only determined by the quality of the products and services offered, but also by the company's ability to manage employee relations, which is part of the internal public relations function. Without a targeted strategy, companies risk facing low motivation and declining performance. This study aims to understand the employee relations strategy of PT. Resultan Karya Indonesia (Rekanesia) in motivating employee work. The theory used refers to Albrecht (2020) which includes internal communication, rewards, career development programs, work flexibility, and conflict resolution mechanisms. The research method uses a descriptive qualitative approach with interview, observation, documentation, and source triangulation techniques. The results show that the employee relations strategy at Rekanesia is implemented through weekly communication forums, one-on-one meetings, providing material and non-material appreciation, flexible working hour policies, and informal activities such as team building. This strategy has been proven to increase employee motivation, satisfaction, and loyalty, thereby creating a productive and conducive work environment. Practically, this research can provide input for PT. Resultan Karya Indonesia to continue strengthening a more effective, participatory, and sustainable internal communication strategy, so that the company is able to face competitive challenges while maintaining its existence in the modern era.